An adaptive cruise control for connected energy-saving electric vehicles. Issue 1 (July 2017) - Bertoni, Lorenzo; Guanetti, Jacopo; Basso, Maria; Masoero, Marco; Cetinkunt, Sabri; Borrelli, Francesco
Abstract: We present an energy-saving cooperative adaptive cruise control (eco-CACC), which minimizes the energy consumption of autonomous electric vehicles. The approach leverages a trajectory preview from the preceding vehicle, and conciliates inter-vehicular distance reduction and speed profile smoothing. The problem is tackled with a nonlinear MPC approach. Rather than tracking a reference trajectory, our approach allows variations of distance and speed between vehicles, as long as the powertrain energy consumption is minimized and collision avoidance is guaranteed. Simulations show that this formulation can successfully handle real-world driving conditions, with limited computational complexity.